De-Industrialization and Trade - Antonio Spilimbergo (Inter-American Development Bank, Office of the Chief Economist, 1995)
Baumol (1967) showed that the rate of growth of an economy slows down if a sector has lower productivity than others and the demand between goods is inelastic. This paper points out that trade is equivalent to technological progress in the tradable sector. Therefore an open economy has higher income but lower growth than a closed economy. Moreover, the reallocation of activity from one country to another country can have a negative effect on welfare when there is country-specific learning by doing.
Keywords: 330